2010
DOI: 10.1002/ange.201005177
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Isolation of Two Isomers of N4CO

Abstract: Inorganic molecules containing polynitrogen chains are known as intrinsically unstable high-energetic compounds. Tetranitrogen (N 4 ) was merely detected as a gaseous metastable molecule with a lifetime of microseconds by neutralization-reionization mass spectrometry, [1] and only a few derivatives of N 4 with open-chain structures-N 4 O, [2] N 4 O 2 , [3] and [N 3 NFO][SbF 6 ] [4] -have been spectroscopically identified. A catenated pentanitrogen unit is found in the N 5 + ion.[5] Its structure and chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
0
14
0
5
Order By: Relevance
“…10 A recent study of the photochemistry of (IV) in solid noble gas matrices showed that (IV) was quickly destroyed, producing N 2 and CO under visible irradiation. In contrast, ArF excimer laser (193 nm) irradiation caused transformation into the open-chain isomers ONCN, ONNC, and NOCN.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 A recent study of the photochemistry of (IV) in solid noble gas matrices showed that (IV) was quickly destroyed, producing N 2 and CO under visible irradiation. In contrast, ArF excimer laser (193 nm) irradiation caused transformation into the open-chain isomers ONCN, ONNC, and NOCN.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By contrast, the triplet ground state carbonyl nitrene intermediate 3 (II) has been obtained only by UV photolysis of (I) isolated in noble gas matrices. 10 The molecular structure of TS2 is similar to that of TS1, in the sense that one of the N 3 ligands is orientated nearly perpendicular to the O−C−N α plane. The most striking differences are related to the C−N α and N α −N β bond lengths ( Figure 6), and the ∠N α CN′ α bond angles.…”
Section: Articlementioning
confidence: 95%
See 1 more Smart Citation
“…[14] Selbst bei Pyrolysetemperaturen von 500 8C blieb etwas Diazid unzersetzt, und es wurden einige neue Banden beobachtet (Abbildung S3 in den Hintergrundinformationen). Durch Vergleich mit dem IR-Spektrum von cyclischem 1, das durch Berechnung anharmonischer Frequenzen auf dem CCSD(T)/ANO2-Niveau vorausgesagt wurde, ließen sich fast alle Banden der neuen Spezies zuordnen (Tabelle 1).…”
unclassified
“…455 nm) ging das Nitren eine Curtius-Umlagerung zu dem N 6 -analogen N 3 -NCO ein. [14] Dieses N 3 -NCO zerfiel bei der Bestrahlung mit UV/Vis-Licht (l ! 335 nm) weiter in CO und N 2 .…”
unclassified